2004
DOI: 10.1128/iai.72.6.3097-3105.2004
|View full text |Cite
|
Sign up to set email alerts
|

Predominant Outer Membrane Antigens of Bartonella henselae

Abstract: A hallmark of Bartonella henselae is persistent bacteremia in cats despite the presence of a vigorous host immune response. To understand better the long-term survival of B. henselae in cats, we examined the feline humoral immune response to B. henselae outer membrane (OM) proteins in naturally and experimentally infected cats. Initially, a panel of sera (n ‫؍‬ 42) collected throughout North America from naturally infected cats was used to probe B. henselae total membranes to detect commonly recognized antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 44 publications
3
39
0
Order By: Relevance
“…Interestingly, the antiapoptotic activity of these supernatants was weaker than the net effect of live B. henselae, hence confirming the role of additional factors that are known to act on the same phenotype and may account for an attenuation of GroEL potency during evolution (like the VirB/D4 T4SS). GroEL was further found to localize to the outer membrane not only of B. bacilliformis but also of B. henselae, and it is highly immunogenic in various Bartonella species (43,84,229,357,432). In addition, it was recognized that Bartonella GroEL harbors a C-terminal phenylalanine that is a general characteristic of outer membrane proteins, indicating that GroEL of Bartonella would be adapted to exposure on the bacterial surface (69,409).…”
Section: The Primary Nichementioning
confidence: 98%
See 1 more Smart Citation
“…Interestingly, the antiapoptotic activity of these supernatants was weaker than the net effect of live B. henselae, hence confirming the role of additional factors that are known to act on the same phenotype and may account for an attenuation of GroEL potency during evolution (like the VirB/D4 T4SS). GroEL was further found to localize to the outer membrane not only of B. bacilliformis but also of B. henselae, and it is highly immunogenic in various Bartonella species (43,84,229,357,432). In addition, it was recognized that Bartonella GroEL harbors a C-terminal phenylalanine that is a general characteristic of outer membrane proteins, indicating that GroEL of Bartonella would be adapted to exposure on the bacterial surface (69,409).…”
Section: The Primary Nichementioning
confidence: 98%
“…In contrast to IalA and CtpA, IalB is an outer membrane protein based on its signal sequence and findings in B. henselae (84), thus seeming to be the natural candidate for the host-interacting component of the invasion-associated locus. Initial results that IalB of B. bacilliformis was located in the inner membrane were surprising for the authors of the study as well and could have been caused by suboptimal growth conditions (100) (31,36,118,136).…”
Section: Infection Of Erythrocytesmentioning
confidence: 99%
“…Culture-based diagnosis of Bartonella infection is even more difficult and time-consuming (21,24), and molecular biology techniques have little practical application outside the research lab. In most of the immunoscreens for diagnostic antigens in Bartonella workers have used pooled sera from a small number of patients without culture-proven infections or sera collected from experimentally infected small animals (8,13).…”
Section: Discussionmentioning
confidence: 99%
“…Infected cats develop a relapsing bacteraemia that may persist for up to 2 years (Breitschwerdt & Kordick, 2000). Previous investigations have shown that B. henselae induces specific humoral and cell-mediated immune responses in naturally or experimentally infected hosts, including cats, humans and mice (Abbott et al, 1997;Arvand et al, 1998aArvand et al, , 2001aChenoweth et al, 2004;Guptill et al, 1999;Regnath et al, 1998). The mechanisms involved in the long-term survival of the bacteria despite vigorous host immune responses are not entirely understood.…”
Section: Introductionmentioning
confidence: 99%